NILAI KARAKTER CERITA ANAK SEBAGAI MEDIA PENGUATAN PENDIDIKAN KARAKTER - Gafur, Abd; Lutfi, Moh; Sapta, Andy; Jameel, Ami Hibatul (Jurnal Bahastra, 2023)
Literature as a function of entertainment and guidance will not be separated from the so-called value. This then underlies the importance of learning literature in elementary schools to instill character education. Literature can be a bridge between teachers and students in schools in an effort to cultivate positive character values. One of the literary works that can be used as a medium for character education in schools is children's stories. This research is a qualitative descriptive research with the object of research in the form of children's story text. The use of a descriptive qualitative approach in this study aims to provide a real and clear picture of the results of an in-depth analysis of the research object. The results of the study show that children's stories can be a bridge or media in strengthening character education in elementary schools. A collection of children's stories entitled "Faldo Si Kleptomania" written by children contains various values, including the values of social care, environmental care, creative discipline, patience and hard work, religious, national spirit, communicative, tolerance, and fond of reading. concise and factual, including research objectives, research methods, results and conclusions.